2000
DOI: 10.1021/ja0005183
|View full text |Cite
|
Sign up to set email alerts
|

Calicheamicin−DNA Recognition:  An Analysis of Seven Different Drug−DNA Complexes

Abstract: A study of calicheamicin γ1 I complexed to seven different recognition sites is presented. The recognition sites encompass a range of oligopyrimidine sites that present different topological features in the minor groove. Intermolecular NOE networks for the different calicheamicin-DNA complexes show that the drug binds in the same mode to each recognition site. Calicheamicin binding also induces a set of characteristic conformational changes in the DNA in each complex that maximize the complementarity of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…This suggestion is consistent with the NMR results. [21][22][23][24][25] Experimental evidence from gel-cleavage studies indicating that the carbohydrate domain of the molecule is responsible for the observed site-specific binding and cleavage was first demonstrated by Drak et al, by comparing the cleavage efficiency of the DNA-bound synthetic aglycon calicheamcinone (6) with that of the DNA-bound intact antibiotic. 26 These researchers found that only 10% of the calicheamicinone molecules abstracted hydrogen from the DNA at a saturating binding concentration of 42 mM.…”
Section: Structural Features Of the Oligosaccharide Responsible For Tmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggestion is consistent with the NMR results. [21][22][23][24][25] Experimental evidence from gel-cleavage studies indicating that the carbohydrate domain of the molecule is responsible for the observed site-specific binding and cleavage was first demonstrated by Drak et al, by comparing the cleavage efficiency of the DNA-bound synthetic aglycon calicheamcinone (6) with that of the DNA-bound intact antibiotic. 26 These researchers found that only 10% of the calicheamicinone molecules abstracted hydrogen from the DNA at a saturating binding concentration of 42 mM.…”
Section: Structural Features Of the Oligosaccharide Responsible For Tmentioning
confidence: 99%
“…All the published NMR studies agree that calicheamicin binds in the minor groove of DNA in an extended conformation with only minor modifications. [21][22][23][24][25] Sugar B binds edgewise deep within the walls of the minor groove as does the aromatic ring C residue with the iodine and orthomethyl group facing toward the bottom of the groove. The thiocarbonyl group linking sugar B to the aromatic C ring is orthogonal to the aromatic ring C as was observed in the X-ray crystal structure of the degradation product 11.…”
Section: Summary Of Structural Features Of the Calicheamicin-dna Complexmentioning
confidence: 99%
“…Sugar diol and amido alcohol arrangements are ''common features'' found in carbohydrates present in antibiotics and anticancer drugs [32,33] that interact with specific sequences of DNA in the minor groove. Their involvement in hydrogen-bonding interactions with the phosphate groups present in the groove has been postulated.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the minor groove at these pyrimidine sequences is topologically diverse and contains different arrays of functional groups, the efforts to understand their mode of action did not produce clear and consistent results. Studies on calicheamicin bound to different DNA duplexes using NMR and biochemical cleavage data revealed that calicheamicin binds to all of the different sequences in the same mode (Kalben et al, 2000). The studies also proposed that calicheamicin binds to a range of oligopyrimidine sequences by the Fig.…”
Section: Calicheamicins and Esperamicinsmentioning
confidence: 93%